2020
DOI: 10.1016/j.jdent.2020.103284
|View full text |Cite
|
Sign up to set email alerts
|

The association between erosive toothwear and gastro-oesophageal reflux-related symptoms and disease: A systematic review and meta-analysis

Abstract: The association between erosive toothwear and gastro-oesophageal reflux-related symptoms and disease: a systematic review and meta-analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 44 publications
2
9
0
9
Order By: Relevance
“…The role of gastroesophageal diseases in the progression of tooth surface loss is much studied. A systematic review and meta-analyses clearly demonstrated that individuals with GER are more likely to have erosive tooth wear compared to controls without GER (Jordão et al, 2020). Alaraudanjoki et al (2016) demonstrated that repeated or prolonged exposure of teeth to gastric acids leads to the selective dissolution of specific components of the tooth surface, causing loss of structure and dentinal hypersensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…The role of gastroesophageal diseases in the progression of tooth surface loss is much studied. A systematic review and meta-analyses clearly demonstrated that individuals with GER are more likely to have erosive tooth wear compared to controls without GER (Jordão et al, 2020). Alaraudanjoki et al (2016) demonstrated that repeated or prolonged exposure of teeth to gastric acids leads to the selective dissolution of specific components of the tooth surface, causing loss of structure and dentinal hypersensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Dentre as formas de prevenção e tratamento da erosão dentária, encontram-se a utilização de produtos fluoretados e a eliminação e controle de fatores etiológicos (Lussi et al, 2019;Carvalho & Lussi, 2020;Jordão et al, 2020). Os produtos fluoretados atuam por meio da formação de CaF2, que age como barreira física e reservatório de íons, dificultando a penetração de ácidos e liberando íons durante desafios erosivos, respectivamente (Lussi et al, 2019).…”
Section: Discussionunclassified
“…O tratamento instiuído no presente caso envolveu quatro sessões de aplicação de verniz fluoretado, o qual possui alta concentração de íons flúor. Entretanto, apenas a utilização de produtos fluoretados não é capaz de impedir o processo de erosão dentária, sendo necessárias medidas para eliminação dos fatores etiológicos e, por vezes, um tratamento multidisciplinar (Magalhães et al, 2011;Barbour & Lussi, 2014;Carvalho & Lussi, 2020;Jordão et al, 2020).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Moreover, individuals with erosive tooth wear will have a negative impact on the quality of life. Hence, referrals to oral health care professionals should be considered from a gastroenterology point of view and vice versa [40]. Other assorted oral findings found consistently in the literature include tooth wear, mouth breathing, tongue thrusting, digital sucking and high arch palate [15,28].…”
Section: Oral Clinical Manifestations Of Rett Syndromementioning
confidence: 99%